The Influence of Material Price Fluctuations on Construction Project Budgeting in Johor Bahru - Song , Mei Xin; Sarpin, Norliana; Masrom, Md. Asrul Nasid; Seow, Ta Wee; Goh, Kai Chen; Sallehuddin, Aina Mardia (Research in Management of Technology and Business, 2026)
Construction sector especially in Johor Bahru has been intensely influenced by the variability and changes of notably crucial construction materials cost such as steel and cement. This phenomenon directly affects budgeting and profitability of the project. This has become an essential and challenging event for G7 contractors. Therefore, this research objectives are to identify the main factors contributing to the price fluctuations of materials in the Johor Bahru construction industry; to identify the effects of material price fluctuations in the Johor Bahru construction industry on financial budgeting in construction projects and to suggest the strategies that can be implemented to reduce the risks associated with material price fluctuations in the Johor Bahru construction industry. The research method of this study is quantitative method where a questionnaire survey was distributed to respondent which is G7 main contractor registered with Construction Industry Development Board (CIDB) in Johor Bahru. A total of 108 responses were obtained which represent a response rate of 17.6%. The collected data were analysed using descriptive statistics analysis with the aid of SPSS software. The results show that changes in government policies, a rise in demand, a shortage of materials, delayed procurement, and global disruptions in substitute supply chains impact most, thereby contributing towards fluctuation in material prices. It is also observed that fluctuation in material prices creates a negative impact upon accurate estimate calculations, budget deficits, financial strain upon project cash flow, decreased profit margins, and slowed down project completion. Lastly, the finding shows that techniques for accommodating price rises, risk-sharing, value engineering, early procurement, joint purchasing, and building long-term vendor ties impact most. However, approaches like the use of price escalation clauses, value engineering, bulk purchasing, and enhancing supplier relationships were identified as being effective in managing risks. In conclusion, the contributions of the proposed study would offer vital perspectives and knowledge for contractors, governments, and relevant stakeholders on improving and enhancing resilient budget and risk management practices in accordance with national transformations within the construction sector.